A cross sectional study of knowledge, attitude and practices related to fixed dose combinations use among clinicians and resident doctors at a tertiary care teaching hospital in India - Belhekar, Mahesh N.; Patel, Tejal C.; Pandit, Prasad R.; Bhave, Kiran A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In the year 2016, Government of India had banned 350 fixed dose combinations (FDCs) for the safety and efficacy purpose. The present study was conducted to assess the knowledge, attitude and practices of the clinicians and residents about the use of FDCs at a tertiary care hospital. Methods: A questionnaire based study was conducted at a tertiary care hospital after getting approval from institutional ethics committee. A pre-validated questionnaire comprising of 30 items was distributed to 100 participants. The questionnaire focused on the prescribing behaviour, knowledge on therapeutic efficacy, advantages and limitations of FDC use, clinician perception regarding FDC use and the strategies to improve the awareness about the regulatory updates of the marketed drugs. Results: Total 52/100 clinicians responded. Out of these, 88% prescribed FDCs in their practice, 62% prescribed FDCs only after ensuring therapeutic efficacy and 50% prescribed WHO approved FDCs. 64% were aware of the recent ban on some FDCs by DCGI. Internet was the most common source of latest updates on the regulatory status of the drug, as stated by 55% clinicians. All clinicians agreed that efforts are needed to ensure that prescribers remain up to date about the post-marketing regulatory status of the drugs. Conclusions: Even though many clinicians prescribe FDCs regularly, they appreciated the step of banning some FDCs; however, the clinicians need to be trained to update themselves regularly. The source and relevance of these updates should be taught to the undergraduate students during their training period which can be reemphasized during post graduate training period.